Identification of novel PI3Kδ inhibitors by docking, ADMET prediction and molecular dynamics simulations. (February 2019) - Liu, Ya-Ya; Feng, Xiao-Yan; Jia, Wen-Qing; Jing, Zhi; Xu, Wei-Ren; Cheng, Xian-Chao
Graphical abstract: The virtual screening, molecular docking, ADMET prediction and molecular dynamics simulations were performed on Asinex database to find the novel compounds against PI3Kδ, which were demonstrated as the following flow chart: Highlights: Phosphoinositide-3-kinase Delta (PI3Kδ) is a well-validated target for anticancer drug design and development. Structure-based virtual screening of ∼300, 000 druglike compounds retrieved from Asinex Gold-Platinum database. A total of 3 potential PI3Kδ-selective inhibitors were identified. Molecular dynamics simulation of their complexes with PI3Kδ suggested their stable binding mode over time. Abstract: Background: Phosphoinositide-3-kinase Delta (PI3Kδ) plays a key role in B-cell signal transduction and inhibition of PI3Kδ is confirmed to have clinical benefit in certain types of activation of B-cell malignancies. Virtual screening techniques have been used to discover new molecules for developing novel PI3Kδ inhibitors with little side effects. Method: Computer aided drug design method were used to rapidly screen optimal PI3Kδ inhibitors from the Asinex database. Virtual screening based molecular docking was performed to find novel and potential lead compound targeting PI3Kδ, at first. Subsequently, drug likeness studies were carried out on the retrieved hits to evaluate and analyze their drug like properties such as absorption, distribution, metabolism, excretion, and toxicity (ADMET) for toxicity prediction. Three least toxic compounds were selected for the molecular dynamics (MD) simulations for 30 ns in order to validate its stability inside the active site of PI3Kδ receptor. Results: Based on the present in silico analysis, two molecules have been identified which occupied the same binding pocket confirming the selection of active site. ASN 16296138 (Glide score: −12.175 kcal/mol, cdocker binding energy: −42.975 kcal/mol and ΔGbind value: −90.457 kcal/mol) and BAS 00227397 (Glide score: −10.988 kcal/mol, cdocker binding energy: −39.3376 kcal/mol and ΔGbind value: −81.953 kcal/mol) showed docking affinities comparatively much stronger than those of already reported known inhibitors against PI3Kδ. These two ligand's behaviors also showed consistency during the simulation of protein-ligand complexes for 30000 ps respectively, which is indicative of its stability in the receptor pocket. Conclusion: Compound ASN 16296138 and BAS 00227397 are potential candidates for experimental validation of biological activity against PI3Kδ in future drug discovery studies. This study smoothes the path for the development of novel leads with improved binding properties, high drug likeness, and low toxicity to humans for the treatment of cancer.